Measurement of ultrasonic velocity in methanol by cavity resonance method - J. KRÓLIKOWSKI; R. PŁOWIEC; J. SINGH; T.K. SAKSENA (Archives of Acoustics, 2014)
The study of cavity resonance of the piezoelectric tubular transducer immersed in liquid has been exploited to evaluate the velocity of ultrasonic wave in methanol. Strong correlation has been proved between cavity resonance frequency and velocity of ultrasonic waves. The results are reported in the temperature range 10-50°C. The presented method is simple and permit the measurements of ultrasonic velocity of liquids at low frequencies.